Exploring the Factors of Workplace Environment Influence Employee Engagement Level: A Thematic Case Study of University Grants Commission, Nepal (Orchid Insights: A Multidisciplinary Journal of Orchid College, 2025)
This study proposed to explore the factors of the workplace environment and their relationship. The environment plays a role in influencing the engagement level of employees in the University Grants Commission, Nepal. UGC Nepal has been a reputed government institution that is authorized to accredit colleges and universities in Nepal. The study followed a qualitative approach in which the researcher adopted thematic analysis. The respondents of the study were permanent and contract staff of UGC, Nepal. The findings explore the themes like work-life balance, team culture and role clarity have been contributing in the workplace environment of UGC while the issues of a culture of unfair treatment based on permanent and contract staff and lack of rewards and recognitions based on the performance result in the lack of motivation and dedication in the employees resulting the low vigor as well. Apart from this, employees are found to be less likely motivated enough to take noble initiatives and are less satisfied with the existing unfair practices of promotion at their perceptual level.